Estudo de caso de viabilidade, projeto e simulação de solução de eletrificação rural com fonte renovável para comunidade ribeirinha do Amazonas - Silva, Josekson Gonçalves da (Brasil, 2025)
This work explores the practicality and cost-effectiveness of introducing a renewable energy-based rural electrification system for riverine communities in the Amazon. The analysis, conducted using HOMER PRO software, examined several hybrid system configurations incorporating solar energy, wind energy, and a diesel generator. The community of Santo Antônio, located in the Environmental Protection Area (APA) of the Rio Negro, approximately 98.49 km as the crow flies from Manaus, and containing 11 families, was chosen as the focus due to its energy needs and significant social importance. The research assessed the sustainability, costs, and environmental impact of each configuration, individually and across generations, aiming to identify solutions that promote energy independence, minimize greenhouse gas emissions, and ensure long-term economic sustainability. The results emphasize that a solar PV system stands out as the ideal choice, providing the lowest total cost, zero emissions, and outstanding energy efficiency. As a result, it is recommended as the most suitable option for the target region of the work.